Proyeksi Kerentanan Banjir Bandang pada Tahun 2045 di Kecamatan Baturiti Kabupaten Tabanan Provinsi Bali - Mardiana, Oriza; Atmaja, Dewa Made; Budiarta, I Gede; Jayantara, I Gst Ngr Yoga; Kurniawan, Wayan Damar Windu (Jurnal Pendidikan Geografi Undiksha, 2025)
The Baturiti District is a district that often experiences flash floods, causing vulnerability in the affected areas. The vulnerability caused by these flash floods includes social vulnerability, physical vulnerability, economic vulnerability, and environmental vulnerability. Therefore, there is a need to project the vulnerability to flash floods in order to minimize the impact in the coming years. This research aims to determine the extent and location of potential flash flood vulnerability in the Baturiti District in the year 2045. The method used in this research is Multi Criteria Decision Analysis (MCDA) according to Regulation No. 2 of 2012 by the National Disaster Management Agency (BNPB). Each parameter is given its respective weight and will be classified using fuzzy logic approach, and for projection, arithmetic growth method and forecast method are used. The results of this research show that the projection of flash flood vulnerability in the Baturiti District in the year 2045 covers an area of 966 hectares. The location with the highest vulnerability area is in the villages of Angseri, Candikuning, Bangli, and Baturiti.